Stem cell therapies: a new era in the treatment of multiple sclerosis - Wu, Lei; Lu, Jing; Lan, Tianye; Zhang, Dongmei; Xu, Hanying; Kang, Zezheng; Peng, Fang; Wang, Jian (Frontiers in Neurology, 2024)
Multiple Sclerosis (MS) is an immune-mediated condition that persistently harms the central nervous system. While existing treatments can slow its course, a cure remains elusive. Stem cell therapy has gained attention as a promising approach, offering new perspectives with its regenerative and immunomodulatory properties. This article reviews the application of stem cells in MS, encompassing various stem cell types, therapeutic potential mechanisms, preclinical explorations, clinical research advancements, safety profiles of clinical applications, as well as limitations and challenges, aiming to provide new insights into the treatment research for MS.